Effect of crosslinking by microbial transglutaminase of gelatin films on lysozyme kinetics of release in food simulants. (August 2022) - Sabaghi, Moslem; Joly, Catherine; Adt, Isabelle; Ozturk, Keziban; Cottaz, Amandine; Degraeve, Pascal
Abstract: The effect of enzymatic crosslinking by microbial transglutaminase on the physico-chemical properties of gelatin-based films incorporated with lysozyme were investigated. Increase in the crosslinking degree of gelatin with microbial transglutaminase concentration in film-forming suspensions was correlated with a decrease of films thickness. Moreover, the enhancement in crosslinking resulted in a decrease of the solubility in water, as well as of the extent of swelling degree, and of the water vapor permeability of films and in an increase of films tensile strength. The kinetics of release at 4 °C of lysozyme from control non-reticulated films and reticulated films to either sodium acetate buffer, or 2% (w/v) agar gels in direct contact were compared. Interestingly, the kinetics of release of lysozyme were always slower from crosslinked films than from control films. This difference was higher for lysozyme release to agar gels, which was dominated by Fickian diffusion. Enzymatic crosslinking by microbial transglutaminase of gelatin-based films incorporated with lysozyme can thus effectively control the release of this food preservative.